Bleeding outcomes after routine transradial primary angioplasty for acute myocardial infarction using eptifibatide and unfractionated heparin: A single‐center experience following the HORIZONS‐AMI trial. Issue 3 (8th April 2013) - Moody, William E.; Chue, Colin D.; Ludman, Peter F.; Chan, Yik‐ki C.; Narayan, Gautam; Millington, Jenna M.; Townend, Jonathan N.; Doshi, Sagar N.
<x xml:space="preserve">Abstract</x> Objectives We sought to (1) determine the bleeding rates after primary percutaneous coronary intervention (PPCI) in our institution, where the default strategy has been transradial (TR) access in combination with unfractionated heparin (UFH) plus eptifibatide, and (2) compare these with the outcomes of patients treated with bivalirudin in HORIZONS‐AMI. Background HORIZONS‐AMI demonstrated that in PPCI undertaken via the transfemoral route, routine use of bivalirudin was associated with lower bleeding rates and improved mortality compared to routine use of UFH plus glycoprotein IIb/IIIa inhibitor (GPI). Methods This was a single‐center prospective registry of consecutive patients undergoing PPCI from January 2009 to August 2011 at the Queen Elizabeth Hospital Birmingham, UK. Thirty‐day major bleeding was defined as per the HORIZONS‐AMI criteria and also according to TIMI and GUSTO scales. Results Of the 432 consecutive patients, 350 fulfilled entry criteria for HORIZONS‐AMI. In contrast with HORIZONS‐AMI, these subjects were older (62.5 ± 13.7 yr vs. 59.8 ± 11.1 yr, P < 0.05) with a higher rate of cardiogenic shock (6.3% vs. 0.8%, P < 0.0001). Despite this higher risk population, the rate of major bleeding was favorable (3.7% [95% CI: 2.0–6.3%] vs. 4.9% [4.0–6.1%], P = 0.32). Similarly, TIMI major bleeding (2.0% [0.8–4.1%] vs. 3.1% [2.3–3.4%], P = 0.10) and GUSTO severe or life‐threatening bleeding (0.6% [0.1–2.5%] vs. 0.4% [0.2–0.9%], P = 0.75) were comparable. Conclusions Routine TR access for PPCI using UFH plus GPI is associated with a low 30‐day rate of major bleeding equivalent to the bivalirudin arm of HORIZONS‐AMI. Default transradial access for PPCI permits routine use of a GPI without the penalty of high bleeding rates. © 2013 Wiley Periodicals, Inc.